Steroid conjugates: Synthesis and preliminary biological testing of pro-juvenoids - Svobodová, Hana; Ryšavá, Hana; Pavlík, Milan; Šaman, David; Drašar, Pavel; Wimmer, Zdeněk (Bioorganic & medicinal chemistry, 2010)
A series of 10 new pro-juvenoids (juvenogens, insect hormonogenic compounds, pro-drug-like agents) was synthesized using isomeric synthetic juvenoids (insect juvenile hormone analogs) and steroid molecules as patterns modifying parts of the complex hormonogenic molecules. In addition, several new synthons were prepared, which were required by the designed synthetic protocol to achieve the target molecules. These pro-juvenoids were subjected to the topical screening tests and to the drinking assays on the red firebug (Pyrrhocoris apterus), a convenient model laboratory phytophagous insect. Simple and efficient synthetic procedures for the preparation of the target pro-juvenoids and their synthons are presented. Furthermore, the biological activity of the pro-juvenoids in comparison with the activity of their parent juvenoids and that of several commercially available agents is demonstrated. Juvenoids and pro-juvenoids may replace toxic insecticides persistent in the insect pest control because they have no adverse effects on non-target organisms and/or human.
Keywords: dezinsekce; Insect Control; Animals; steroidy; zvířata; Heteroptera; juvenilní hormony; vztahy mezi strukturou a aktivitou; Steroids; Juvenile Hormones; Structure-Activity Relationship